Systemy jakości produktów rolnych i środków spożywczych w świetle nowej regulacji prawnej - Leśkiewicz, Katarzyna (Wydawnictwo Naukowe UAM, 2013)
The subject of this paper is quality schemes for agricultural products and foodstuffs in light of Regulation (EU) No 11/51/2012 of the European Parliament and the Council of 21 November 2012. Although agricultural products quality may be approached in different ways, no definition of the concept has been provided in the Regulation. The approach to the quality of agricultural products and foodstuffs employed in the Regulation, on the one hand, is a continuation and strengthening of the earlier views on quality, but it also, on the other hand, combines quality schemes with consumer information, support extended to agricultural producer and fair competition. The legal solutions proposed in the Regulation have been divided into mandatory and optional, which may lead to a conflict between quality and high quality, since quality becomes a resultant outcome of the features referred to in legal acts rather than an added value.

L’oggetto delle considerazioni è la qualità dei prodotti agricoli e alimentari alla luce del nuovo regolamento del Parlamento europeo e del Consiglio (UE) n. 1151/2012 del 21 novembre 2012 in materia di regimi dei prodotti agricoli e alimentari. La qualità dei prodotti agricoli può essere affrontata su diverse superfici, il legislatore però non ha decise di introdurre la definizione della qualità. Le nuove norme, tuttavia, mostrano un nuovo approccio del legislatore alla qualità dei prodotti agricoli e alimentari, da una parte consolidando le direzioni precedentemente indicate nella politica della qualità, dall’altra parte unendo i regimi di qualità con le informazioni destinate ai consumatori, con il sostegno ai produttori e alla concorrenza leale. Le soluzioni giuridiche riguardanti la qualità sono state divise in volontarie e obbligatorie, il che può causare il divario tra qualità e alta qualità dei prodotti. La qualità diventa la risultante delle caratteristiche, dei requisiti descritti negli atti giuridici, piuttosto che un valore aggiunto.
Quality schemes for agricultural products and other foodstuffs in light of the new EU regulation
I regimi di qualità dei prodotti agricoli e alimentari alla luce della nuova regolazione giuridica